A context-specific social and emotional learning programme to support adolescents following the transition to secondary school. (2nd October 2021) - Mahmud, Arif
ABSTRACT: Research demonstrates that pupils do not always have the necessary social and emotional intelligence to cope with the transition to secondary school successfully. This paper explores a context-specific intervention designed to enhance key social and emotional skills after a secondary school transition. The intervention was designed with reference to a school-context analysis of children who had recently transitioned to secondary school. Sixty children aged 11–12 years took part in the intervention which involved six group sessions and the outcomes of the intervention were assessed through pre-, post-, and follow-up self-report questionnaires. Focus groups were also conducted with intervention participants following completion of the programme. Findings demonstrate that the intervention had a significant positive impact on empathy. The focus group findings highlighted ways the intervention helped pupils to address negative emotions, cope and manage difficult problems as well as positive and negative implementation strategies for future interventions. The paper highlights a context-specific approach to support programmes, based on the inclusion of an exploratory phase when designing such interventions. The findings may be of benefit to practitioners, researchers and educational psychologists.